2003
DOI: 10.1074/jbc.m305952200
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of the Angiotensin II Type 1 Receptor Alters the Spatial Proximity of Transmembrane 7 to the Ligand-binding Pocket

Abstract: Activation of G protein-coupled receptors by agonists involves significant movement of transmembrane domains (TM) following binding of agonist. The underlying structural mechanism by which receptor activation takes place is largely unknown but can be inferred by detecting variability within the environment of the ligand-binding pocket, which constitutes a water-accessible crevice surrounded by the seven TM helices. Using the substituted cysteine accessibility method, we initially identified those residues with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 39 publications
(43 reference statements)
4
70
0
Order By: Relevance
“…7 However, TM7 shifts away from the ligand-binding pocket in the AT 1 -N111G receptor, 10 implying that the conformation of AT 1 receptor during stretch-induced activation is different from that of the constitutively active AT 1 receptor. In general, GPCRs are structurally flexible and unstable, and multiple conformational states exist during the GPCR activation process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 However, TM7 shifts away from the ligand-binding pocket in the AT 1 -N111G receptor, 10 implying that the conformation of AT 1 receptor during stretch-induced activation is different from that of the constitutively active AT 1 receptor. In general, GPCRs are structurally flexible and unstable, and multiple conformational states exist during the GPCR activation process.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, studies using substituted cysteine accessibility mapping (SCAM) showed that conformation of the AT 1 p-ERKs during stretch-induced activation is quite different from that of the AT 1 -N111G receptor. 7,10 Transmembrane domain 7 (TM7) of the AT 1 receptor undergoes a counterclockwise rotation and a shift toward the ligand-binding pocket in response to mechanical stretch, 7 but it shifts away from the ligand-binding pocket in the AT 1 -N111G receptor. 10 In this study, we show that, as an inverse agonist, olmesartan strongly inhibits the stretch-induced activation of the AT 1 receptor, as well as the constitutive activity of the AT 1 -N111G receptor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although using SCAM to probe receptor structure has its shortcomings, the method has been applied to a number of GPCRs, including D2 dopamine receptor, A1 adenosine receptor and AT1 angiotensin II receptors [for example, (5,13,(54)(55)(56)], for which no X-ray crystal structures are available. Coupled with rhodopsin-based molecular modeling, SCAM analysis has proven to be very useful for elucidating the structures of GPCRs.…”
Section: Limitations Of Scammentioning
confidence: 99%
“…As reported previously (26), the various concentrations of MTSEA had very little effect (no more than a 20% reduction at high MTSEA concentrations) on the binding properties of the wild-type AT 1 receptor, which contains 10 endogenous cysteines (Fig. 1).…”
Section: F170cmentioning
confidence: 55%